The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-11790-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel pfk13 polymorphisms in Plasmodium falciparum population in Ghana

Abstract: The molecular determinants of Plasmodium falciparum artemisinin resistance are the single nucleotide polymorphisms in the parasite’s kelch propeller domain, pfk13. Validated and candidate markers are under surveillance in malaria endemic countries using artemisinin-based combination therapy. However, pfk13 mutations which may confer parasite artemisinin resistance in Africa remains elusive. It has therefore become imperative to report all observed pfk13 gene polymorphisms in malaria therapeutic efficacy studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Typically, areas with high transmission intensity show increased exchange of genetic material amongst the parasite population which subsequently leads to the development of spontaneous mutations that can confer resistance to antimalarial drugs ( 5 , 61 ). In addition, the observation of both zone-specific and shared mutations across the zones may indicate gene flow amongst individuals in the population through intra-country migration ( 5 , 6 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, areas with high transmission intensity show increased exchange of genetic material amongst the parasite population which subsequently leads to the development of spontaneous mutations that can confer resistance to antimalarial drugs ( 5 , 61 ). In addition, the observation of both zone-specific and shared mutations across the zones may indicate gene flow amongst individuals in the population through intra-country migration ( 5 , 6 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis of the P. falciparum genome revealed mutations in the kelch propeller gene (pfk13) to be associated with the development of parasite tolerance to ART and are being monitored in parasite populations as markers of drug resistance (2,4). ART resistance pfk13 candidate mutations and novel ones have been reported in Ghanaian isolates (5)(6)(7). A study conducted in Cambodia has also shown parasites with increased ring stage survival but lacking the pfk13 mutations which implies that there could be other genes involved and/or different resistance mechanisms (8).…”
Section: Introductionmentioning
confidence: 99%
“…This study did not detect pfk13 propeller domain mutations in the 29 parasite isolates. Since most pfk13 mutations detected earlier in Ghana appeared as low-frequency mutations (Matrevi et al, 2019;Matrevi et al, 2022), molecular surveillance of pfk13 mutations may require more extensive sampling efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the mutations are validated single nucleotide polymorphisms (SNPs), used as molecular markers for the surveillance of artemisinin-resistant malaria parasites (F446L, N458Y, M476I, Y493H, R539T, I543T, P553L, R561H, P574L, C580Y) (WHO, 2019). Recently, P. falciparum parasites carrying the validated SNPs F446I, M476I, P553L, R561H, P574L, C580Y and A675V have emerged and expanded or been identified in Africa [22], in Angola, Ghana [23], Mali, Rwanda [24][25][26][27]. In Mozambique, available studies on the prevalence of pfK13 SNPs, refer to parasite samples collected prior to 2018 [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%